Relevant Information and Managerial Performance: The Moderating Role of Accounting System Digitalization in State-Owned Banks - Irga Anugrah Safira Harahap; Paul Usmany; Jefry Gasperz (LP2M IAIN Palopo, 2026)
This study aims to examine the effect of job relevant information on managerial performance and to analyze the moderating role of accounting system digitalization in state-owned banks (Bank BUMN). Grounded in contingency theory, the study hypothesizes that job relevant information positively influences managerial performance and that accounting system digitalization strengthens this relationship. A quantitative research design with a survey method was employed. Data were collected using structured questionnaires from 40 employees of Bank BUMN in Jambi City who were directly involved in accounting and reporting activities. The data were analyzed using moderated regression analysis to test both direct and interaction effects among variables. The results show that job relevant information has a positive and significant effect on managerial performance, indicating that the availability of task-relevant information supports effective managerial decision-making. However, accounting system digitalization does not moderate the relationship between job relevant information and managerial performance. These findings suggest that the effectiveness of managerial performance is primarily determined by the quality and relevance of information rather than the level of system digitalization alone. The study contributes to the development of management accounting literature by highlighting the contingent role of digitalization in the public banking context. Practically, the results imply that Bank BUMN should prioritize improving the quality of job relevant information while aligning digital accounting systems with managerial decision-making needs. Future research is encouraged to expand the research context and incorporate additional contingency factors to further explain variations in managerial performance.